Shortlisting putative candidate genes underlying qDTY1.1, a major effect drought tolerant QTL in rice (Oryza sativa L.) - Krishna Sai Karnatam, Deepa Jaganathan, Kambale Rohit Dilip, Manikanda Boopathi N and Raveendran Muthurajan (Electronic Journal of Plant Breeding, 2020)
Drought is one of the major constraints affecting rice (Oryza sativa L.) productivity and production. Conventional breeding is leading to slow progress in developing drought tolerant varieties. In this context, mapping consistent major effect QTLs and unraveling molecular basis of those QTLs will pave way for deployment of those QTLs into breeding applications. Out of more than 2500 drought tolerance related QTLs, hardly 5 to 10 QTLs have been put into breeding applications due to larger QTL window, lack of tightly linked markers and lack of knowledge on candidate genes underlying QTLs. In this present study, in silico analysis was carried out to characterize a major effect QTL qDTY1.1 region on chromosome 1 for its gene content, drought responsiveness of genes in the QTL window and metabolic functions. Out of 352 genes residing in the qDTY1.1 window, 50% of the genes were found to be drought responsive. Bioinformatics search identified precise drought responsive expression pattern of 100 genes in the QTL window. Fifty seven genes were found to be up regulated and forty three genes were found to be down regulated. The qDTY1.1 region is found to contain 23 drought responsive transcription factors such as WRKY, bZIP, NAC, AP2 and C2H2. These drought responsive genes are confirmed for the possession of drought responsive cis elements like DRE, ABRE, MYB and MYC.